1989
DOI: 10.1115/1.3226542
|View full text |Cite
|
Sign up to set email alerts
|

A Stress Singularity Parameter Approach for Evaluating the Interfacial Reliability of Plastic Encapsulated LSI Devices

Abstract: Since the stress and displacement fields near a bonding edge show singularity behaviors, the adhesive strength evaluation method, using maximum stresses calculated by a numerical stress analysis such as the finite element method, is generally not valid. In this paper, a new method, which uses two stress singularity parameters, is presented for evaluating adhesive strength. This method is applied to several kinds of molded models, composed of epoxy base resin and Fe-Ni alloy sheets, and plastic encapsulated LSI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(26 citation statements)
references
References 3 publications
0
26
0
Order By: Relevance
“…The works of Dunn et al (1997a, b) provide experimental correlation of A 1 (and possibly A 2 ) to fracture initiation in the case that α 1 and α 2 are real and the singular points are V-notches in isotropic materials. Hattori et al (1989Hattori et al ( , 1991 propose a two-parameter failure law based on A 1 and the exponent α 1 for V-notch configurations, and demonstrated that a good correlation is achieved with experimental results. Reedy and Guess (1995, and the references therein), correlated failures of adhesive-bonded butt tensile joints with A 1 .…”
Section: Introductionmentioning
confidence: 86%
“…The works of Dunn et al (1997a, b) provide experimental correlation of A 1 (and possibly A 2 ) to fracture initiation in the case that α 1 and α 2 are real and the singular points are V-notches in isotropic materials. Hattori et al (1989Hattori et al ( , 1991 propose a two-parameter failure law based on A 1 and the exponent α 1 for V-notch configurations, and demonstrated that a good correlation is achieved with experimental results. Reedy and Guess (1995, and the references therein), correlated failures of adhesive-bonded butt tensile joints with A 1 .…”
Section: Introductionmentioning
confidence: 86%
“…Further, it may not be considered appropriate to represent an uncracked specimen by a cracked one. The use of a stress singularity parameter, equivalent to stress intensity factor in a cracked body, at the bi-material corner point was investigated by Groth and Brottare [18], Hattroi et al [19] and Lefebvre and Dillard [20]. However, the shortcomings of this stress singularity parameter are its dependence on the strength of the singularity and its variation with mode mixity.…”
Section: Introductionmentioning
confidence: 99%
“…The delamination due to the stress concentration brings about fatal malfunction in the device. The linear elastic fracture mechanics (LEFM) concept is utilized for the evaluation of the interface strength at the edge (3), (4) . The size of a singular stress region near an interface edge is dependent on the film thickness (5), (6) .…”
Section: Introductionmentioning
confidence: 99%